Extra gingival pyogenic granuloma: An unusual case presentation - Kumar Gupta, Gaurav; Rai, Puja; Umapathy, Deepak; Shivhare, Peeyush (Journal of Chitwan Medical College, 2025)
Oral pyogenic granuloma represents an exaggerated soft tissue response and vascular proliferation resulting from chronic low-grade irritation.Its incidence is relatively common and accounts for 3.81% to 7% of all biopsy findings from oral cavity lesions. The most frequent intraoral localization is the gingiva, but the lesions can occur on the lips, tongue, buccal mucosa, and palate. Fewer than 5% of exophytic soft tissue lesions submitted for histopathological examinations are pyogenic granulomas. Hormones play a role in the etiology of the lesion in the setting of pregnancy (where the lesion is named a pregnancy tumor). There is increased incidence of these lesions towards the end of pregnancy (when levels of circulating estrogens are highest), and they tend to shrink after delivery (when there is a precipitous drop in circulating estrogens). Clinically, oral pyogenic granuloma occurs as a smooth or lobulated exophytic lesion manifesting as small, red, erythematous papules on a pedunculated or sometimes sessile base, which is usually hemorrhagic. Their friable, hemorrhagic, and frequently ulcerated appearance correlates with their histologic structure. This article reports an unusual case of extra gingival pyogenic granuloma occurring on the right buccal mucosa in a male patient.